2017
DOI: 10.3390/ijms18112289
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by the Curcumin Analogue EF-24 Is Neither Mediated by Oxidative Stress-Related Mechanisms nor Affected by Expression of Main Drug Transporters ABCB1 and ABCG2 in Human Leukemia Cells

Abstract: The synthetic curcumin analogue, 3,5-bis[(2-fluorophenyl)methylene]-4-piperidinone (EF-24), suppresses NF-κB activity and exhibits antiproliferative effects against a variety of cancer cells in vitro. Recently, it was reported that EF-24-induced apoptosis was mediated by a redox-dependent mechanism. Here, we studied the effects of N-acetylcysteine (NAC) on EF-24-induced cell death. We also addressed the question of whether the main drug transporters, ABCB1 and ABCG2, affect the cytotoxic of EF-24. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Accumulating evidence suggests EF24 to be active in cell and/or tumor models of numerous cancer types. For example, in in-vitro experiments, it is effective in inhibiting osteogenic sarcoma cells (31), malignant pleural mesothelioma cells (32), progressive medullary thyroid cancer cells (33), human pancreatic cancer cells (34) and leukemia/lymphoma cells (20, 35). Whether used alone or in combination with other agents, EF24 displays great potential as an anti-cancer therapeutic.…”
Section: Biological Activities and Mechanisms Of Action Of Ef24mentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests EF24 to be active in cell and/or tumor models of numerous cancer types. For example, in in-vitro experiments, it is effective in inhibiting osteogenic sarcoma cells (31), malignant pleural mesothelioma cells (32), progressive medullary thyroid cancer cells (33), human pancreatic cancer cells (34) and leukemia/lymphoma cells (20, 35). Whether used alone or in combination with other agents, EF24 displays great potential as an anti-cancer therapeutic.…”
Section: Biological Activities and Mechanisms Of Action Of Ef24mentioning
confidence: 99%
“…Therefore, it seems that the role of EF24 in ROS induction may be cell type-dependent, and more evidence is needed to clarify these contradictory results. Interestingly, Skoupa et al recently concluded that apoptosis induced by the EF-24 is not mediated by oxidative stress-related in human leukemia cells (20). A redox-dependent-mediated mechanism only marginally contributes to the EF24-induced apoptosis in K562 cells.…”
Section: Biological Activities and Mechanisms Of Action Of Ef24mentioning
confidence: 99%
See 1 more Smart Citation
“…CLEFMA causes death in lung cancer cells via ROS production and activation of multiple apoptotic effector molecules [19,20,21,22]. EF24 also kills cancer cells by signaling through multiple apoptotic mechanisms, but the role of ROS production in EF24-mediated cell death is uncertain [23,24,25]. Although cisplatin, CLEFMA, and EF24 affect similar components in apoptotic signaling pathways, dissimilarities between cisplatin and these curcuminoids have been identified, including their effect on glutathione signaling, which is implicated in cisplatin-resistance [1,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis can also be induced in human leukaemia cells by the curcumin analogue EF-24. In their study, Skoupa and colleagues [ 17 ] investigate the mechanism by which EF-24 induces cell death in K562 cells. They propose that EF-24 may be suitable as an anticancer agent, specifically in cases of drug resistance.…”
mentioning
confidence: 99%